Survival, dispersal and reproduction of headstarted Mona Island iguanas, Cyclura cornuta stejnegeri (2007)
The endemic Mona Island Iguana, Cyclura cornuta stejnegeri, is considered endangered, and exhibits relatively low population numbers and reduced recruitment of juveniles to adults. A headstarting program was initiated in 1999 to increase the effective population number. Two groups of headstarted iguanas were released in April and August 2002, after reaching a target size. Most of the released iguanas have since been observed to be active and in good health. Two females bred in 2004, the first certain record of reproduction by headstarted Cyclura iguanas in the wild. Eight radiotracked individuals had large dispersal ranges, with mean Minimum Convex Polygon (MCP) of 10.7 ha (range 2.6-22.2 ha) and mean distances covered of 288 m (range 471-6396 m).We discuss the future development of the headstarting program for Mona Island iguanas.